The reutilization of expired waste zinc gluconate for ZnO/C anode in lithium-ion battery. Issue 1 (15th October 2019) - Hou, Hongying; Wang, Lei; Meng, Kun; Qiu, Jinxu; Zhu, Jing
Abstract : Zinc gluconate is widely used as a nutrient because the zinc ion (Zn 2+ ) participates in the synthesis of enzymes. However, the improper management of expired waste zinc gluconate could result in the influx of excessive zinc ions into the environment and thus cause damage to organisms. For this purpose, expired waste zinc gluconate was first recycled through a hydrothermal reaction and pyrolysis for a zinc oxide (ZnO)/carbon (C) composite. Furthermore, the effect of the hydrothermal reaction time on the morphology and electrochemical performance of the zinc oxide/carbon composite was also investigated. The results showed that the combination mode of zinc oxide with carbon microspheres could be controlled by tailoring the hydrothermal reaction time. The carbon content of the composite with a hydrothermal time of 5 h (ZnO/C-5h) was 53 wt%, slightly lower than the 55 wt% of the composite with a hydrothermal time of 9 h (ZnO/C-9h). Resultantly, the ZnO/C-5h anode exhibited higher electrochemical performance due to better phase interface. For example, the reversible discharge capacity of the ZnO/C-5h anode remained 270 mAh/g at 1000 mA/g for 500 cycles, higher than the 183 mAh/g of the ZnO/C-9h anode. Better phase interface and the synergistic effect may contribute to better electrochemical performance. These results could provide a recycling paradigm for expired waste zinc gluconate.